Theoretical aspects and practical recommendations for forming an innovative system of a construction enterprise - Prykhodko, D.O.; Kurykin, O.Yu.; Shepeta, M.O.; Kuzmich, Y.L.; Kuznetsov, O.I. (Ways to Improve Construction Efficiency, 2023)
The modern construction sector is undergoing rapid transformation under the influence of technological changes, digitalization and globalization of economic processes. Innovative development is a key factor in ensuring the competitiveness of construction enterprises, as it allows to increase production efficiency, optimize costs and improve the quality of final products. The formation of an enterprise’s innovative system involves the integration of the latest technologies, adaptation of organizational structures and the development of strategic approaches to managing innovative activities. The theoretical aspects of this process are based on the analysis of the conceptual foundations of innovation management, the methodology for introducing modern technologies into the construction industry and the assessment of their impact on the overall productivity of the enterprise. The study of innovative development models allows us to identify key elements of an effective system: the implementation of digital platforms, process automation, the use of environmentally friendly materials and the application of artificial intelligence technologies in the management of construction projects. Practical recommendations for the formation of an innovative system of a construction enterprise include the creation of an adaptive organizational structure that contributes to the rapid adoption of management decisions and the development of a corporate culture focused on innovation. One of the important stages is the development of mechanisms for financing innovative projects, attracting investments and implementing flexible business models. Particular attention should be paid to the development of human resources, which involves improving the skills of employees, stimulating their creative activity and implementing a motivation system for participation in innovative renewal processes. Therefore, the effective formation of an innovative system of a construction enterprise requires an integrated approach that includes strategic planning, technological renewal and the creation of a favorable environment for the development of innovations. The development and implementation of modern management tools in the construction industry will contribute to increasing the competitiveness of enterprises and ensuring sustainable development of the construction sector in conditions of dynamic market changes.